Somatic variability in wild boar (Sus scrofa L.) in different areas of Central Italy - Settimio Adriani; Fioravante Serrani; Andrea Amici (Italian Journal of Animal Science, 2010)
A survey of wild boar shot during two consecutive years (hunting seasons 2002-2004) was carried out in order to evaluate which somatic measurements are most significant in identifying and discriminating among different morphotypes in central Italy. Biometric data from 688 wild boars was collected in three different areas of central Italy, two in Viterbo and one in the Province of Rieti. The following somatic measurements were individually recorded for each specimen: head-body length, height at withers, hind-foot length, ear length, ear-snout distance and ear-shoulder distance. Body weight was registered, and age was estimated from tooth eruption and wear. The animals were divided into three age classes; young (aged less then 12 months), sub-adults (aged between 12 and 36 months), and adults (36 months and older). After a preliminary ANOVA procedure, which did not give satisfactory results, a statistical analysis was performed using a canonical discriminant procedure, given an a priori classification (geographical area) and several quantitative variables (somatic measurements and weight). The separation between areas was estimated calculating the squared distance of Mahalanobis. The data referring to all 688 specimens was subjected to factor analysis. The results of the canonical discriminant analysis highlight the existence of two distinct groups within all three age classes. There is a statistically significant difference between the southern- Maremma (SM) vs. the Apennine (A) and sub- Apennine (SA) areas, for young (P<0.0001), sub-adults (P<0.001) and adults (P<0.001). The difference between the A and SA areas was significant only for sub-adults (P<0.05). The first canonical variable account for 92.5, 92.7 and 89.9% of the total variance for the three age classes respectively, but this is unequally correlated with the original variables suggesting that the separation between the two areas is due to differences in conformation rather than in body size. On the basis of the discriminant analysis large part of the animals were correctly categorised in the sampling areas. As regards the factor analysis results for the adult group, the first three common factors are able to explain 78, 92, and 64% of the covariance for the data of the SM, A and SA groups respectively. These results suggest that, for the SM group, a differentiation among morphotypes may be possible on the basis of a few somatic measurements. These results confirm the need for biochemical and genetic studies to identify if the different morphotypes refer to the autochthonous wild boar strain.